Final Exams and Their Effects on the Development of Primary School Students - Marta, Fendra; Rasyid, Willadi; Padli; Putra, Aldo Naza; Ockta, Yovhandra (Universitas Jambi, Indonesia, 2024)
This research aimed to analyze the effect of final exams on the development of sixth graders in primary school. The ex post facto method was employed in this research to identify and analyze the causal relationship between final exams and various aspects of student development. The researchers purposively sampled, considering student characteristics pertinent to the research objectives. The researchers analyzed the collected data descriptively to paint a clear and detailed picture of students' conditions before, during, and after final exams. The results showed diverse student conditions relevant to their overall development, including cognitive, emotional, social, and physical aspects. These findings highlight the importance of paying attention to the holistic condition of students during the exam period, not just focusing on academic results alone. Proper and comprehensive support during this period is essential to ensure optimal and sustainable student development.